Higher Levels of Cystatin C Are Associated with Worse Cognitive Function in Older Adults with Chronic Kidney Disease: The Chronic Renal Insufficiency Cohort Cognitive Study1. Issue 9 (14th August 2014) - Yaffe, Kristine; Kurella‐Tamura, Manjula; Ackerson, Lynn; Hoang, Tina D.; Anderson, Amanda H.; Duckworth, Mark; Go, Alan S.; Krousel‐Wood, Marie; Kusek, John W.; Lash, James P.; Ojo, Akinlolu; Robinson, Nancy; et al.
<x xml:space="preserve">Abstract</x> Objectives To determine the association between cognition and levels of cystatin C in persons with chronic kidney disease (CKD). Design Prospective observational study. Setting Chronic Renal Insufficiency Cohort Cognitive Study. Participants Individuals with a baseline cognitive assessment completed at the same visit as serum cystatin C measurement (N = 821; mean age 64.9, 50.6% male, 48.6% white). Measurements Levels of serum cystatin C were categorized into tertiles; cognitive function was assessed using six neuropsychological tests. Scores on these tests were compared across tertiles of cystatin C using linear regression and logistic regression to examine the association between cystatin C level and cognitive performance (1 standard deviation difference from the mean). Results After multivariable adjustment for age, race, education, and medical comorbidities in linear models, higher levels of cystatin C were associated with worse cognition on the modified Mini‐Mental State Examination, Buschke Delayed Recall, Trail‐Making Test Part (Trails) A and Part B, and Boston Naming (P < .05 for all). This association remained statistically significant for Buschke Delayed Recall (P = .01) and Trails A (P = .03) after additional adjustment for estimated glomerular filtration rate (eGFR). The highest tertile of cystatin C was associated with greater likelihood of poor performance on Trails A (odds ratio (OR) = 2.17, 95% confidence interval (CI) = 1.16–4.06), Trails B (OR = 1.89, 95% CI = 1.09–3.27), and Boston Naming (OR = 1.85, 95% CI = 1.07–3.19) than the lowest tertile after multivariate adjustment in logistic models. Conclusion In individuals with CKD, higher serum cystatin C levels were associated with worse cognition and greater likelihood of poor cognitive performance on attention, executive function, and naming. Cystatin C is a marker of cognitive impairment and may be associated with cognition independent of eGFR.